2017
DOI: 10.1089/ten.tec.2017.0200
|View full text |Cite
|
Sign up to set email alerts
|

Fixation of Hydrogel Constructs for Cartilage Repair in the Equine Model: A Challenging Issue

Abstract: The use of AFG should be preferred to xenogeneic products in the horse, but AFG is subject to individual variations and laborious to make. The PCL anchor provides the best fixation; however, this technique involves the whole osteochondral unit, which entails a different conceptual approach to cartilage repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 52 publications
0
55
0
Order By: Relevance
“…The stiffness of both the zonal- and non-zonal constructs at implantation was comparable in our study, which may explain why the amount of bone loss was also comparable in those groups. A comparable issue with PCL-reinforced constructs has been described by Mancini et al and was partially affiliated to the xenogenic fibrin glue [29]. By using a solid press-fit fixation without glue, we were able to eliminate this variable.…”
Section: Discussionmentioning
confidence: 72%
“…The stiffness of both the zonal- and non-zonal constructs at implantation was comparable in our study, which may explain why the amount of bone loss was also comparable in those groups. A comparable issue with PCL-reinforced constructs has been described by Mancini et al and was partially affiliated to the xenogenic fibrin glue [29]. By using a solid press-fit fixation without glue, we were able to eliminate this variable.…”
Section: Discussionmentioning
confidence: 72%
“…[ 19 ] Similarly, a handheld extrusion printer has been developed to simultaneously deliver mesenchymal stromal cells (MSCs) and gelatin-methacryloyl (GelMA) hydrogels into chondral defects in a single-session surgery. [ 17 ] Although promising, both studies demonstrated that the integration of the printed constructs to the native host tissue remained a significant issue, [ 20 ] and in general, the in vivo stability and integration of tissue engineered constructs remains a major challenge in the field of cartilage regeneration. [20–22] Importantly, while stable axial integration can be achieved for treatment strategies targeting osteochondral defect repair, i.e., through anchoring in the subchondral bone, [ 20 ] to achieve a reliable lateral integration within the chondral region is a particularly daunting task.…”
Section: Introductionmentioning
confidence: 99%
“…[ 17 ] Although promising, both studies demonstrated that the integration of the printed constructs to the native host tissue remained a significant issue, [ 20 ] and in general, the in vivo stability and integration of tissue engineered constructs remains a major challenge in the field of cartilage regeneration. [20–22] Importantly, while stable axial integration can be achieved for treatment strategies targeting osteochondral defect repair, i.e., through anchoring in the subchondral bone, [ 20 ] to achieve a reliable lateral integration within the chondral region is a particularly daunting task. This type of integration is especially challenging when using hydrogels or bioinks that display optimal cell embedding properties and thus low mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Absence of an adhesive like fibrin glue allowed us to avoid any biocompatibility issues except for those from the construct itself. This may be especially important due to the fact that fibrin glue has shown to produce negative effects such as inferior tissue quality, lower defect filling, and fibrocartilage formation [ 14 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…PCL-reinforcement has also shown promising results for chondral and osteochondral regeneration in vivo [ 12 , 13 ]. However, to date, in vivo studies with PCL-reinforced constructs in large animal models have been limited due to an insufficient fixation within the cartilage defect [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%